Apparatus difficulty in rhythmic gymnastics routines - comparison between 2 Olympic cycles - Leandro, C. (Science of Gymnastics Journal, 2018)
The aim of this study was to analyze the evolution of the apparatus difficulty in Rhythmic Gymnastics gymnasts in 2 Olympic cycles and identify eventual factors that could contribute to improve the performance quality in competition. We studied the value of the apparatus difficulty in the gymnasts (potentially the gymnasts could participate in the Olympic Games) of the first World Championships of each cycle (2012/2016 e 2016/2020). This analysis focused on the technical value of the apparatus difficulty performed by the gymnasts in a total of 288 competition routines in the World Championships 2013, and 200 competition routines in the World Championships 2017. The data was treated using the descriptive statistics and after checking the normality of the data distribution using the Kolmogorov-Smirnov test we used a ttest to determine whether there were significant differences between the World Championships. Results showed an increasing appreciation of the apparatus difficulty in the final score of the gymnasts. The apparatus difficulty elements were significantly increased from one cycle to the other, mainly due to the increase of the Mastery value. There`s a greater balance in the use of different elements, giving privilege to the apparatus technique. The increase on the value of the apparatus difficulty in the RG competition routines will contribute for the quality and diversity of the RG competition in the Olympic Games.